Hypoxia Differentially Affects Healthy Men and Women During a Daytime Nap With a Dose-Response Relationship: a Randomized, Cross-Over Pilot Study - Riveros-Rivera, Alain; Penzel, Thomas; Gunga, Hanns-Christian; Opatz, Oliver; Paul, Friedemann; Klug, Lars; Boschmann, Michael; Mähler, Anja (Frontiers in Physiology, 2022)
CONTEXT: The use of daytime napping as a countermeasure in sleep disturbances has been recommended but its physiological evaluation at high altitude is limited. OBJECTIVE: To evaluate the neuroendocrine response to hypoxic stress during a daytime nap and its cognitive impact. DESIGN, SUBJECTS, AND SETTING: Randomized, single-blind, three period cross-over pilot study conducted with 15 healthy lowlander subjects (8 women) with a mean (SD) age of 29 (6) years (Clinicaltrials identifier: NCT04146857, https://clinicaltrials.gov/ct2/show/NCT04146857?cond=napping&draw=3&rank=12 ). INTERVENTIONS: Volunteers underwent a polysomnography, hematological and cognitive evaluation around a 90 min midday nap, being allocated to a randomized sequence of three conditions: normobaric normoxia (NN), normobaric hypoxia at FiO2 14.7% (NH15) and 12.5% (NH13), with a washout period of one week between conditions. RESULTS: Primary outcome was the interbeat period measured by the RR interval with electrocardiogram. Compared to NN, RR during napping was shortened by 57 ms and 206 ms under NH15 and NH13 conditions, respectively (p<0.001). Sympathetic predominance was evident by heart rate variability analysis and increased epinephrine levels. Concomitantly, there were significant changes in endocrine parameters such as erythropoietin (~6 UI/L) and cortisol (~100 nmol/L), (NH13 vs NN, p<0.001). Cognitive evaluation revealed changes in the color-word Stroop test. Additionally, although sleep efficiency was preserved, polysomnography showed lesser deep sleep and REM sleep, and periodic breathing, predominantly in men. CONCLUSION: Although napping in simulated altitude does not appear to significantly affect cognitive performance, sex-dependent changes in cardiac autonomic modulation and respiratory pattern should be considered before napping is prescribed as a countermeasure.